Comparison of arch length and width in the angle Class II malocclusion with extraction and non-extraction in the Dental Hospital Universitas Airlangga - Hamid, Thalca; Adhim, Muhammad Fauzan; Alida, Alida (Indonesian Journal of Dental Medicine, 2024)
Background: Depending on the disparity seen, orthodontic treatments frequently take into account the possibility of tooth extraction or non-extraction. Class II Angle malocclusion cases are the specific emphasis of this study, whereas Class I Angle malocclusion patients were the focus of earlier research. Purpose: Examining how tooth extraction and non-extraction therapies affect arch length in patients with Class II Angle malocclusion is the goal. Method: Arch length was measured using pre- and post-treatment models of individuals with Class II Angle malocclusion who had extraction and nonextraction treatments. To find out if there were any notable variations, the collected data was analyzed. Results: The maxillary and mandibular arch lengths in the extraction group were significantly different before and after orthodontic treatment (p<0.05). Likewise, the the widths of the mandibular and maxillary arches before and after orthodontic treatment were significantly different (p<0.05). The maximum and arch length in the non-extraction group had a signifiant different before and after orthodontic treatment (p<0.05). Conclusion: the sagittal arch length decreased in both extraction and nonextraction treatments, the arch width decreased in extraction treatments, and the arch width increased in non-extraction treatments. In patients with Class II malocclusion, there are notable changes in the sagittal arch width and length before and after orthodontic treatment, whether extraction or non-extraction. Compared to the non-extraction treatment group, the extraction treatment group experienced more substantial alterations in sagittal arch length and width.